Collectin CL-P1 utilizes C-reactive protein for complement activation - Roy, Nitai; Ohtani, Katsuki; Matsuda, Yasuyuki; Mori, Kenichiro; Hwang, Insu; Suzuki, Yasuhiko; Inoue, Norimitsu; Wakamiya, Nobutaka (Biochimica et biophysica acta, 2016)
C-reactive protein (CRP) is a plasma pentraxin family protein that is massively induced as part of the innate immune response to infection and tissue injury. CRP and other pentraxin proteins can activate a complement pathway through C1q, collectins, or on microbe surfaces. It has been found that a lectin-like oxidized LDL receptor 1 (LOX-1), which is an endothelial scavenger receptor (SR) having a C-type lectin-like domain, interacts with CRP to activate the complement pathway using C1q. However it remains elusive whether other lectins or SRs are involved in CRP-mediated complement activation and the downstream effect of the complement activation is also unknown. We prepared CHO/ldlA7 cells expressing collectin placenta-1 (CL-P1) and studied the interaction of CRP with cells. We further used ELISA for testing binding between proteins. We tested for C3 fragment deposition and terminal complement complex (TCC) formation on HEK293 cells expressing CL-P1. Here, we demonstrated that CL-P1 bound CRP in a charge dependent manner and the interaction of CRP with CL-P1 mediated a classical complement activation pathway through C1q and additionally drove an amplification pathway using properdin. However, CRP also recruits complement factor H (CFH) on CL-P1 expressing cell surfaces, to inhibit the formation of a terminal complement complex in normal complement serum conditions. The interaction of collectin CL-P1 with CFH might be key for preventing attack on “self” as a result of complement activation induced by the CL-P1 and CRP interaction. •CL-P1 interacts with C-reactive protein.•CL-P1 mainly utilizes the collagen-like and coiled-coil domain to interact with CRP.•CL-P1 is involved in CRP mediated complement activation through the classical and amplification pathway.•The complement factor H recruited by CRP on CL-P1 expressing cells might prevent the terminal complement complex formation.